Interventions and provocations : conversations on art, culture, and resistance - Harper, Glenn, 1946- (SUNY series, interruptions--border testimony(ies) and critical discourse/s., 1998)
This book presents interviews with some of the most provocative artists of the postmodern era. These sculptors, writers, filmmakers, activists, and performance artists have forged a new vision of art that is confrontational, political, and concerned with interrupting the domination of our lives by mass culture.